"How Ya Gonna Keep 'Em Down on the Farm, After They've Seen Paree?" World War I Overseas Military Service and Rural Americans' Postwar Occupational Mobility. Issue 1 (2nd January 2022) - Cunningham, Angela R.
Abstract : In the aftermath of World War I, U.S. discourse was animated by the concern that demobilized soldiers, having experienced the world outside of their hometowns, would resist returning to farms and to their preinduction occupations. Did military service really encourage an occupational shift? Were rural individuals especially susceptible to and was emplacement in foreign locales especially culpable for this change, as popular culture suggested? Focusing on North Dakota, a state with unusually detailed World War I records, this article uses a novel linked census–military data set and statistical analysis to examine how individuals' place-based military experience might have inflected their postwar occupational mobility. Whereas univariate models support the contemporary perception that farm boys with overseas service were less likely to remain in agriculture, increasingly complex models suggest more nuanced interpretations, with civilian individual and contextual characteristics and their interaction being significantly predictive of farm leaving. Addressing substantive gaps in World War I historiography by contextualizing neglected subpopulations, this research also shows the value of using quantitative methods to engage with critical military geographies. Operationalizing theories of place–individual co-constitution through the analysis of longitudinal, individual data demonstrates how interest in soldiers' experiences and in the spatiotemporally distant effects of war can be productively intertwined.